Yield, nutrition, and leaf gas exchange of lettuce plants in a hydroponic system in response to Bacillus subtilis inoculation - Oliveira, Carlos Eduardo da Silva [UNESP]; Jalal, Arshad [UNESP]; Aguilar, Jailson Vieira [UNESP]; de Camargos, Liliane Santos [UNESP]; Zoz, Tiago; Ghaley, Bhim Bahadur; Abdel-Maksoud, Mostafa A.; Alarjani, Khaloud Mohammed; AbdElgawad, Hamada; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP] (Frontiers, 2023)
Inoculation with Bacillus subtilis is a promising approach to increase plant yield and nutrient acquisition. In this context, this study aimed to estimate the B. subtilis concentration that increases yield, gas exchange, and nutrition of lettuce plants in a hydroponic system. The research was carried out in a greenhouse in Ilha Solteira, Brazil. A randomized block design with five replications was adopted. The treatments consisted of B. subtilis concentrations in nutrient solution [0 mL “non-inoculated”, 7.8 × 103, 15.6 × 103, 31.2 × 103, and 62.4 × 103 colony forming units (CFU) mL−1 of nutrient solution]. There was an increase of 20% and 19% in number of leaves and 22% and 25% in shoot fresh mass with B. subtilis concentrations of 15.6 × 103 and 31.2 × 103 CFU mL−1 as compared to the non-inoculated plants, respectively. Also, B. subtilis concentration at 31.2 × 103 CFU mL−1 increased net photosynthesis rate by 95%, intercellular CO2 concentration by 30%, and water use efficiency by 67% as compared to the non-inoculated treatments. The concentration of 7.8 × 103 CFU mL−1 improved shoot accumulation of Ca, Mg, and S by 109%, 74%, and 69%, when compared with non-inoculated plants, respectively. Inoculation with B. subtilis at 15.6 × 103 CFU mL−1 provided the highest fresh leaves yield while inoculation at 15.6 × 103 and 31.2 × 103 CFU mL−1 increased shoot fresh mass and number of leaves. Concentrations of 7.8 × 103 and 15.6 × 103 increased shoot K accumulation. The concentrations of 7.8 × 103, 15.6 × 103, and 31.2 × 103 CFU mL−1 increased shoot N accumulation in hydroponic lettuce plants.
Keywords: biological nitrogen fixation; growth-promoting bacteria; Lactuca sativaL; photosynthetic efficiency; water use efficiency